Virulence Factors of Escherichia Coli: A Comprehensive Review - Abdulkhaleq , Aya watheq; Nafil , Yaqeen kadhim; fadel , Hanen abas; Mohammad , Duaa Mahdi; Hassan, Ola Saber; Shwayel , Aqeel Jabbar (American Journal of Biology and Natural Sciences, 2025)
Escherichia coli (E. coli), a diverse and adaptable gram-negative bacterium, is widely recognized for its dual role as a commensal organism and a major pathogen responsible for a variety of intestinal and extraintestinal infections. Despite decades of research, a comprehensive understanding of its virulence mechanisms and regulatory networks remains incomplete. This review synthesizes recent developments in E. coli pathogenesis, focusing on key virulence factors such as adhesins, toxins, iron uptake systems, invasion mechanisms, and immune evasion strategies. By analyzing molecular genetics, host-pathogen interactions, and resistance patterns across multiple E. coli pathotypes, including UPEC, EHEC, and EPEC, the study highlights how mobile genetic elements, regulatory systems, and environmental pressures drive virulence expression and antibiotic resistance. The findings underscore the urgent need for integrated diagnostic tools, surveillance strategies, and alternative therapeutic interventions such as vaccines and anti-virulence therapies. This review provides critical insight into the multifactorial nature of E. coli pathogenicity and guides future research in combating its public health impact.